Is there an excess of significant findings in published studies of psychotherapy for depression? - Flint, J; Cuijpers, P; Horder, J; Koole, S; Munafò, MR (Cambridge University Press, 2015)
BACKGROUND: Many studies have examined the efficacy of psychotherapy for major depressive disorder (MDD) but publication bias against null results may exist in this literature. However, to date, the presence of an excess of significant findings in this literature has not been explicitly tested. METHOD: We used a database of 1344 articles on the psychological treatment of depression, identified through systematic search in PubMed, PsycINFO, EMBASE and the Cochrane database of randomized trials. From these we identified 149 studies eligible for inclusion that provided 212 comparisons. We tested for an excess of significant findings using the method developed by Ioannidis and Trikalinos (2007), and compared the distribution of p values in this literature with the distribution in the antidepressant literature, where publication bias is known to be operating. RESULTS: The average statistical power to detect the effect size indicated by the meta-analysis was 49%. A total of 123 comparisons (58%) reported a statistically significant difference between treatment and control groups, but on the basis of the average power observed, we would only have expected 104 (i.e. 49%) to do so. There was therefore evidence of an excess of significance in this literature (p = 0.010). Similar results were obtained when these analyses were restricted to studies including a cognitive behavioural therapy (CBT) arm. Finally, the distribution of p values for psychotherapy studies resembled that for published antidepressant studies, where publication bias against null results has already been established. CONCLUSIONS: The small average size of individual psychotherapy studies is only sufficient to detect large effects. Our results indicate an excess of significant findings relative to what would be expected, given the average statistical power of studies of psychotherapy for major depression.